Caracterização histológica de folhas de Mentha pulegium x spicata (Lamiaceae) - Martins, M. B G [UNESP] (2003)
The glandular hairs of Mentha pulegium x spicata (Lamiaceae) were studied by light microscopy and scanning electron microscopy, Three morphologically distinct types of trichomes are described: two of them are glandulars (peltate and capitate) and one is non-glandular hair (tector). Capitate trichome is of Type I, and consists of a foot cell, a stalk and a unicellular head with elongated format and two lateral depressions, showing the thinnest cuticle. The peltate trichome consists of a foot cell, a stalk cell and a radial cluster of secretory cells, cover by cuticle. The tector trichomes can be simple and forked -format, both multicellular, in which there are ornamentations on cell cuticle. The leaf cross sections, analysed in light microscopy, showed mesophyll organized for unistratification palisade parenchyma and lacurary parenchyma with four to five cell stratum. It was observed the presence of cristal mass agglomerate in mesophyll cells and in epidermical cells.